Zero Overstaying: Harapan Baru Pasca Lahirnya Undang-Undang Nomor 22 Tahun 2022 Tentang Pemasyarakatan - Rizki Bagus Prasetio; Renny Waskita; Jody Imam Rafsanjani; Zaihan Harmaen Anggayudha (Jurnal Ilmiah Kebijakan Hukum, 2023)
In practice, the release of detainees by law has not been optimal, and it results in overstaying. The authority of the head of the detention center to release detainees has diminished, leading to administrative procedures and coordination issues among law enforcers. This study addresses and analyzes the problem, exploring improvements following the enactment of Law 22 of 2022 on Corrections. Adopting a normative juridical research approach, it examines the extensive discretion granted by the Criminal Procedure Code to law enforcers, often prioritizing detention without considering alternatives. Inefficient coordination during detainee release, delays in responding to expiration notices, and non-compliant implementing regulations highlight system inefficiency. This causes hesitation in releasing detainees and discomfort with other law enforcement agencies. The Special Prison Planning Team and a stronger correctional system aim to promote collaboration and equal footing. Stricter regulations are necessary to protect detainees' rights on release and provide tailored services.